Detecting the Role of Agriculture and Industry Value Added, Energy, Capital Flow, and Openness to Trade upon Environmental Kuznets Curve for India - Sharmiladevi, J. C. (International Journal of Energy Economics and Policy, 2024)
This study revisits the environmental Kuznets curve for India, considering unique variables like agriculture and industry value added, fossil fuel energy consumption, inward foreign direct investment, openness to trade, economic growth and carbon dioxide (CO2) emission. The study results indicate the presence of EKC for India, indicating a positive long-term equilibrium relationship between agriculture and industry value added and fossil fuel energy consumption with CO2 emission. Inward FDI and trade openness have a negative relation with CO2 emission, supporting the fact that the environmental regulations for international investments and trade in India are becoming more assertive. At the same time, India needs stringent regulations on emissions from the agriculture and industry sectors.